Köln Sammelt : Zeitgenössische Kunst aus Kölner Privatbesitz. (Köln : Museum Ludwig, 1988)
Beuys, Joseph ; Broodthaers, Marcel ; Fautrier, Jean ; Fontana, Lucio ; Kawara, On ; Kounellis, Jannis ; Manzoni, Piero ; Merz, Mario ; Michaux, Henri ; Palermo, Blinky ; Polke, Sigmar ; Rainer, Arnulf ; Tapies, Antoni ; Tuttle, Richard ; Twombly, Cy
Köln Sammelt : Zeitgenössische Kunst aus Kölner Privatbesitz, Museum Ludwig, Köln, 5. November bis 11. Dezember 1988
boek
Keywords: Duitsland; Köln